Efektivitas Pelayanan Penarikan Pajak Melalui “Samperin Cak” di UPT Pengelolaan Pendapatan Daerah Lumajang - Dimas Ilham Akbari; Sri Roekminiati; Sapto Pramono; Aris Sunarya (Lembaga Pengembangan Kinerja Dosen, 2025)
Tax collection is one of the critical sources of regional revenue to support development. The Regional Revenue Management Technical Implementation Unit (UPT) of Lumajang launched an innovative program called “Samperin Cak” (Pick-Up Tax Service System) to enhance tax collection effectiveness. This study aims to analyze the effectiveness of the “Samperin Cak” program in improving taxpayer compliance, reducing tax arrears, and increasing regional revenue. The research method used is qualitative with a descriptive approach. Data were collected through interviews, observations, and documentation. The results indicate that the “Samperin Cak” program effectively reaches taxpayers with limited access to service offices. Moreover, the program has increased public satisfaction with tax services. However, challenges such as limited human resources and operational vehicles need to be addressed promptly. The study recommends increasing budget allocation for program operations and conducting more extensive public outreach.